2022
DOI: 10.1002/acr.24618
|View full text |Cite
|
Sign up to set email alerts
|

Patient Acceptance of Nurse Practitioners and Physician Assistants in Rheumatology Care

Abstract: Objective To assess whether patients with autoimmune disease would accept advanced practice providers (APPs) as an option to fill the growing shortage of rheumatologists. Methods We administered a cross‐sectional survey to 500 patients or parents of children who reported having been diagnosed with qualifying autoimmune conditions and who had seen their primary rheumatology providers in the past 6 months. Respondents self‐reported whether their primary providers were rheumatologists or APPs. Our analysis compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This finding is consistent with previous research on patient satisfaction with PAs in a variety of medical practice settings. [6][7][8][9][10][11][12][13] A 2016 study found that 77.7% of participants reported having a positive quality experience with PAs. 35 Similarly, 77.9% of participants said their experience being treated by an NP was positive, and 81.5% reported positive experiences with physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous research on patient satisfaction with PAs in a variety of medical practice settings. [6][7][8][9][10][11][12][13] A 2016 study found that 77.7% of participants reported having a positive quality experience with PAs. 35 Similarly, 77.9% of participants said their experience being treated by an NP was positive, and 81.5% reported positive experiences with physicians.…”
Section: Discussionmentioning
confidence: 99%
“…5 Research on patient acceptance of and satisfaction with PAs spans more than 5 decades, consistently showing that patients are satisfied with the care delivered by PAs. [6][7][8][9][10][11][12][13] However, previous research explored patient satisfaction with PAs in specific practice settings such as hospitals, outpatient primary care clinics, and EDs. 11 Fewer national survey efforts have been conducted exploring the general public's experiences with and perceptions of PAs.…”
mentioning
confidence: 99%